Apoyo como pasante de ingeniería civil en la secretaria de planeación de Pesca – Boyacá (2023)
This document is presented as a dissemination article in the modality of internship in the Civil Engineering career of the Antonio Nariño University, which aims to carry out the internship in the Planning Secretary of the municipality of Pesca Boyacá, with the purpose of supporting the supervision of infrastructure projects and administrative tasks assigned through technical verification and applicability of procedures established by the entity, developing activities such as budgeting, site visits, drafting of technical documents, construction monitoring, administrative tasks such as carrying out certifications of land use, nomenclature, stratification, supervision reports, work monitoring records and documentary inventory as well as actively participating in projects and programs of the entity developed through a mixed methodology (qualitative and quantitative) based on the identified needs. The activities carried out are presented through the results contained in this document and the work log referred to inthe annexes, which includes a photographic record and evidence of the activities carried out, these under the supervision of the planning secretary of the municipality of Pesca Boyacá.